2017
DOI: 10.4014/jmb.1610.10008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Gamma-Aminobutyric Acid by Optimizing Culture Conditions of Lactobacillus brevis HYE1 Isolated from Kimchi, a Korean Fermented Food

Abstract: This study evaluated the effects of culture conditions, including carbon and nitrogen sources, L-monosodium glutamate (MSG), and initial pH, on gamma-aminobutyric acid (GABA) production by HYE1 isolated from kimchi, a Korean traditional fermented food. HYE1 was screened by the production analysis of GABA and genetic analysis of the glutamate decarboxylase gene, resulting in 14.64 mM GABA after 48 h of cultivation in MRS medium containing 1% (w/v) MSG. In order to increase GABA production by HYE1, the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 34 publications
4
51
0
2
Order By: Relevance
“…which was in agreement with a previous study reporting 2% maltose and 3% tryptone for the optimum GABA production by L. brevis HYE1 [51]. Furthermore, another previous study reported that when the glutamate concentration in the culture medium was in excess of 500 mM, glutamate would inhibited the GABA production of the strain L. paracasei NFRI 7415, which was isolated from a Japanese traditional fermented fish (funasushi) at a maximum concentration of 302 mM [15].…”
Section: Gaba Production On Glutamate-reinforced Mediumsupporting
confidence: 92%
See 1 more Smart Citation
“…which was in agreement with a previous study reporting 2% maltose and 3% tryptone for the optimum GABA production by L. brevis HYE1 [51]. Furthermore, another previous study reported that when the glutamate concentration in the culture medium was in excess of 500 mM, glutamate would inhibited the GABA production of the strain L. paracasei NFRI 7415, which was isolated from a Japanese traditional fermented fish (funasushi) at a maximum concentration of 302 mM [15].…”
Section: Gaba Production On Glutamate-reinforced Mediumsupporting
confidence: 92%
“…Most previous studies on the optimization of GABA production by LAB reported yeast extract as an optimal nitrogen source. However, it should be noted that the mixed nitrogen sources of tryptone and yeast extract have occasionally been reported to be optimal nitrogen sources for GABA production by LAB [51]. Diverse carbon sources have been previously optimized according to GABA-producing LAB strains, such as 1% glucose for L. buchneri MS, 4% sucrose for L. sakei B2-16, and 3% sucrose for L. brevis 340G [19].…”
Section: Gaba Production On Glutamate-reinforced Mediummentioning
confidence: 99%
“…Tamura et al [ 22 ] developed a fed-batch fermentation method for the efficient biotransformation of monosodium l -glutamate (MSG) by Enterococcus avium G-15, in which the final GABA content reached 115.7 g/L after 72 h. Shi et al [ 23 ] established a cell biotransformation process for converting a mixed substrate (80 g/L l -glutamic acid plus 240 g/L MSG) into GABA by high levels of rinsed L. brevis TCCC13007 resting cells, generating 201 g/L GABA. MSG has been widely applied to GABA fermentation processes [ 22 24 ], possibly due to its good solubility.…”
Section: Introductionmentioning
confidence: 99%
“…As GABA is formed as a by-product of food fermentations, LAB, which play an eminent role the fermentation of a wide range of different products, are of particular importance when talking about GABA-enriched food. Hence it is not surprising that strains isolated from various fermented food source had first been shown to have the ability to produce GABA, for example L. namurensis NH2 and P. pentosaceus NH8 from nham [19], L. paracasei NFRI 7415 from Japanese fermented fish [20], L. paracasei PF6, Lactococcus lactis PU1 and L. brevis PM17 from cheese [28], L. brevis 119-2 and L. brevis 119-6 from tsuda kabu [12], and recently many studies focused on the identification of novel GABA-producing LAB and investigated the biochemical properties of GAD from different strains in more detail [12,14,15,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%